2019
DOI: 10.5194/acp-19-14149-2019
|View full text |Cite
|
Sign up to set email alerts
|

Different strategies to retrieve aerosol properties at night-time with the GRASP algorithm

Abstract: Abstract. This study evaluates the potential of the GRASP algorithm (Generalized Retrieval of Aerosol and Surface Properties) to retrieve continuous day-to-night aerosol properties, both column-integrated and vertically resolved. The study is focused on the evaluation of GRASP retrievals during an intense Saharan dust event that occurred during the Sierra Nevada Lidar aerOsol Profiling Experiment I (SLOPE I) field campaign. For daytime aerosol retrievals, we combined the measurements of the ground-based lidar … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 78 publications
4
33
0
1
Order By: Relevance
“…Due to its proximity to the African continent, Granada region is frequently affected by Saharan dust intrusions, especially in summer (Mandija et al, 2017;Valenzuela et al, 2015). These African dust intrusions usually transport large mineral dust loads to our study area (e.g., Benavent-Oltra et al, 2019;Lyamani et al, 2006). During the analysed period, there was an intrusion of Saharan dust over the region of study from 24 to 27 June, as confirmed by CALIMA warning system (www.calima.ws; Fig.…”
Section: Case Study: Npf During Saharan Dust Intrusionsupporting
confidence: 63%
“…Due to its proximity to the African continent, Granada region is frequently affected by Saharan dust intrusions, especially in summer (Mandija et al, 2017;Valenzuela et al, 2015). These African dust intrusions usually transport large mineral dust loads to our study area (e.g., Benavent-Oltra et al, 2019;Lyamani et al, 2006). During the analysed period, there was an intrusion of Saharan dust over the region of study from 24 to 27 June, as confirmed by CALIMA warning system (www.calima.ws; Fig.…”
Section: Case Study: Npf During Saharan Dust Intrusionsupporting
confidence: 63%
“…A study that compared the GRASP retrieval scheme employed here against in situ measurements showed that the differences were less than 30 % for the different retrieval schemes (Benavent-Oltra et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…For example, in this study, the implemented retrieval allows us to observe the variability of columnar properties during the night. In contrast, in similar retrieval realized by Benavent-Oltra et al (2019), any variability of columnar properties through the night was not considered.…”
Section: Lidar Datamentioning
confidence: 99%
“…The last few decades have seen unprecedented efforts to better characterize aerosol particle properties and aerosol radiative effects with in situ and remote sensing observations. For example, in situ measurements based on a wide variety of techniques, such as photoacoustic and cavity ring-down spectrometers, filter-based photometers, and polarized imaging nephelometers, have provided detailed information on size, shape, and absorption for many different regions across the world and continue to do so (Bergstrom et al, 2007;Bond et al, 1999;Dubovik et al, 2000;Espinosa et al, 2017Espinosa et al, , 2018Moosmüller et al, 2005;Petzold et al, 2005;Rocha-Lima et al, 2014;Snider et al, 2015). However, in situ measurements have limitations due to the small sampling volumes that they represent and are very limited in number and spatial coverage.…”
Section: Introductionmentioning
confidence: 99%